Antiferromagnetic Ordering at Room Temperature in Co-Doped Sb2Te3 Topological Insulators - Singh A.; Ghosh A.K.; Chatterjee S. (My University, 2025)
Structural and magnetic properties of Co-doped Sb2Te3 topological insulators have been investigated. Surface morphology was studied using scanning electron microscope (SEM) and atomic force microscope (AFM). X-ray photo electron spectroscopy (XPS) study reveals the mixed states of Co in Co2+ and Co3+. Magnetic study indicates that the substitution of Co in Sb2Te3 not only tune the materials from diamagnetic to antiferromagnetic (even at room temperature) but also propose a promising materials for antiferromagnetic TI which may be useful even for room temperature applications. © 2017, Springer Science+Business Media, LLC, part of Springer Nature.